Towards a Revision of the Second Period of Quakerism - Moore, Rosemary Anne (Quaker studies, 2012)
W.C. Braithwaite’s The Second Period of Quakerism is over ninety years old, and remains the standard work on Quakerism in the later seventeenth century and the beginning of the eighteenth. This paper suggests possible contents for a new book on the Quaker history of that period. It would deal with Quakerism as it was on both sides of the Atlantic. It would draw on the many books, articles and theses now available on particular aspects of this time, but its authors would also need to undertake new research. In particular, there is archive material requiring exploration, and a study of George Whitehead is urgently needed.